2013
DOI: 10.1111/scs.12067
|View full text |Cite
|
Sign up to set email alerts
|

Being in transit and in transition The experience of time at the place, when living with severe incurable disease ‐ a phenomenological study

Abstract: The aim of this study is to describe the experience of time as it presents itself at the place being situated when living with severe incurable disease and receiving palliative care. The empirical data consist of 26 open‐ended interviews with 23 patients receiving palliative care at home, at a palliative day care, in a palliative bed unit in hospital or in a nursing home in Norway. A common meaning of a shifting space for living emerged from the analysis and was revealed through three different aspects: (i) Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
0
17
0
2
Order By: Relevance
“…However, the recipients themselves have no control over the attainment of this outcome, resulting in the sense that life spent living with the device is stuck or on hold. This sense of being stuck in time is at odds with our natural state of being-in-theworld which is to always be moving forwards (Ellingsen et al 2014). The VAD itself demands attention, its needs must become a central feature around which recipients' lives and time is organised; failure to do so is to risk their life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the recipients themselves have no control over the attainment of this outcome, resulting in the sense that life spent living with the device is stuck or on hold. This sense of being stuck in time is at odds with our natural state of being-in-theworld which is to always be moving forwards (Ellingsen et al 2014). The VAD itself demands attention, its needs must become a central feature around which recipients' lives and time is organised; failure to do so is to risk their life.…”
Section: Discussionmentioning
confidence: 99%
“…This paper focuses on the experience of time and identity following the implantation of a VAD. There is often a tendency for the temporal elements of chronic illness to be dismissed (Gergel, 2013), and a need has been highlighted for health care professionals to develop a more nuanced understanding of patients' temporal experience (Shubin et al 2015;Ellingsen et al 2014). A review of experiences of time in chronic illness identified four structures, of which calendar or clock time is the most frequently used, which may lead us to believe that this has the greatest impact on the individual (Jowsey, 2016).…”
Section: Phenomenology and Timementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that patients in transition to end-of-life care experience a time which they deem ‘unsafe’15 suggesting there is a need to provide a safe environment and sensitive unrushed conversations and to view ACP as a process to support patients during this transition period and prevent a sense of abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge for health workers is to not take for granted that the individual will experience time in a typical and traditional way. How individuals experience time even in the face of death is as diverse as life itself, but nevertheless it may be important to note that patients' understanding of time may be associated with their existence and not with a time schedule where structuring and synchronization are essential, such as in in hospitals (Ellingsen,et al 2013b) . The experience of time…”
Section: Relevance To Clinical Practicementioning
confidence: 99%